Reproductive biology of two marine catfishes (Siluriformes, Ariidae) in the Sepetiba Bay, Brazil - Iracema David Gomes; Francisco Gerson Araújo (Revista de Biología Tropical, 2004)
Marine catfish are abundant in the Sepetiba Bay, a 305 km 2 area in Southeast Brazilian coast (Lat. 22º 54’-23º 04’S; Long. 43 o 44’-44 o 10’W), but the knowledge on their biology is still scanty. The reproductive biology of Sciadeichthys luniscutis (Valenciennes 1840) and Genidens genidens (Valenciennes 1839) was studied through monthly sampling, from October 1998 to September 1999. Fishes were caught with a standardized otter trawl, in the interior of Sepetiba Bay, and near to the confluence with a major freshwater contributor. Six gonadal stages were described, based on macroscopic observations of gonad form, size, weight, color and oocyte diameter, and microscopic observations of differences in size and staining in the nucleus and cytoplasm structures, as viewed through a light microscope. Changes in the gonadosomatic index (GSI) and in stages of gonadal development showed what S. luniscutis spawned in Spring, while G. genidens spawned in Summer. Total spawning was shown for both species as indicated by high concentration of post-ovulatory follicles in spent stages. Fecundity was low (14-38 vitellogenic oocytes for S. luniscutis and 6-24 for G. genidens), when compared with other teleosts. Low fecundity and separation in spawning period suggest that both species are k-strategist, able to avoid interspecific competition in early stages of life cycle to optimize the use of the available niche El pez-gato de mar es abundante el la Bahía Sepetiba, un área de 305 km² en la costa del sureste brasileño, pero el conocimiento de su biología es aun escaso. La biología reproductiva de Sciadeichthys luniscutis y Genidens genidens fue estudiada a través de muestreos mensuales, desde octubre de 1998 a setiembre de 1999. Los peces fueron capturados con una red barredera estandarizada, en el interior de la Bahía Sepetiba, y cerca de la confluencia con un río tributario principal. Seis estadíos gonadales fueron descritos, basados en observaciones macroscópicas de diferencias en el tamaño y tinción del núcleo y estructuras citoplasmáticas, observadas a través del microscopio de luz. Los cambio en el índice gonadosomático () y en los estadíos del desarrollo gonadal, mostraron que S. Luniscutis desova en primavera, mientras que G. genidens desova en verano. El desove fue evidenciado en ambas especies por una alta concentración de folículos post-ovulatorios en los estadios maduros. La fecundidad fue baja (14-38 oocitos vitelogénicos en S. luniscutis y 6-24 en G. genidens) cuando se la compara con otros teleósteos. La baja fecundidad y la separación en el período de desove sugiere que ambas especies tienen estrategia-k, capaces de evitar competencia interespecífica en los primeros estadíos del ciclo de vida, para optimizar el uso del nicho disponible Os bagres marinhos constituem um dos mais abundantes recursos pesqueiros da Baía de Sepetiba (Lat.22º54’-23º04’S, Long.43º34’-44º10’O), porém o conhecimento da biologia é escasso. Abiologia reprodutiva de Sciadeichthys luniscutis (Valenciennes, 1840) e Genidens genidens (Valenciennes, 1839) foi estudada através de amostragens mensais entre outubro-1998 e setembro- 1999. Os peixes foram capturados em coletas de arrasto de fundo na Baía de Sepetiba e com redes de espera, na confluência com o rio da Guarda. Foram descritas 6 fases de desenvolvimento gonadal, com base em observações macroscópicas de forma, tamanho, peso, cor e diámetro dos ovócitos, e observações microscópicas de diferenças de tamanho das estruturas celulares. Variações no índice gonadossomático (IGS) e nos estádios de desenvolvimento gonadal indicaram que S. luniscutis desova na primavera, enquanto G. genidens desova no verão. A desova total apresentada por ambas espécies, foi indicada pela elevada concentração de folículos pós-ovulatórios em ovários desovados. A fecundidade foi baixa (14-38 ovócitos vitelogênicos para S. luniscutis e 6-24 para G. genidens), quando comparada a outros teleósteos. A tendência de desenvolvimento da estratégia K foi desenvolvida por ambas espécies caracterizada pelo grande tamanho dos ovócitos, baixa fecundidade, elevada proteção à prole e separação temporal no período reprodutivo, podendo ser um mecanismo para evitar competição interespecífica na Baía de Sepetiba, por estas abundantes espécies tão proximamente relacionadas